Filosofi Pete: Mengurai Makna Tersembunyi dan Strategi Dekonstruksi Stigma dalam Iklan Tokopedia - Indika Putri Lestari; Nanda Aulia Ningtyas; Galih Putra Pamungkas (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2026)
Advertising serves not only as a commercial medium but also as a site of ideological construction. The “Filosofi Pete” advertisement, produced by Ernest Prakasa and released by Tokopedia in 2021, employs the analogy of pete (Parkia speciosa) to challenge the persistent stigma surrounding Indonesian local products. This study aims to reveal the hidden meanings and stigma deconstruction strategies embedded in the advertisement through Roland Barthes’ semiotic framework. Employing a qualitative-descriptive research d esign, the study systematically analysed 14 selected visual scenes using the three-tier model of denotation, connotation, and myth proposed by Barthes. The findings demonstrate that the advertisement constructs a counter-narrative against the colonial mindset that positions local products as inferior. Key strategies identified include (1) emotional narrative arc from aversion to acceptance, (2) inversion of negative sensory associations, (3) juxtaposition of stigmatised objects within prestigious contexts, and (4) typographic integration of local symbols into brand identity. These strategies collectively deconstruct the myth of local product inferiority while repositioning Tokopedia as a cultural mediator for UMKM empowerment. This study contributes to the growing literature on semiotic analysis of Indonesian digital advertising and local brand nationalism.